Islam Serta Resolusi Konflik Berbasis Kearifan Lokal Masyarakat Jawa dan Sunda - Muharis, Muharis; Akhda, Najmu Tsaqib (Medan Resource Center, 2022)
This study aims to find out how the basis of Muslims in conducting conflict resolution based on local wisdom in multireligious society in Java and Sunda. In addition, this study also aims to find out how the conflict resolution model based on local wisdom in multireligious society developed by Muslims in both areas. This research is a qualitative research. The approach used is phenomenological. Data collection techniques used observation and in-depth interviews. The results show that the conflict resolution model developed by Muslims in multireligious society in Java and Sunda always put forward local wisdom in the area. Local wisdom that is in line with the values contained in the teachings of Islam rahmatan lil alamin. Local wisdom and Islamic values are the barriers to the various potential conflicts in society.